The Haynes automotive heating & air-conditioning systems manual : the Haynes repair manual for automotive heating and air-conditioning systems - Stubblefield, Mike.; Haynes, John H. (John Harold) (Sparkford, Nr, Yeovil, Somerset, England : Haynes Pub., Group ; Newbury Park, Calif.: Haynes Publications, 2011)
A guide to automotive heating and air conditioning that provides instructions for system maintenance, troubleshooting, and repairs.
Includes index.
Keywords: Automobiles -- Heating and ventilation -- Handbooks, manuals, etc; Automobiles -- Air conditioning -- Handbooks, manuals, etc